Modelling of an advanced charging system for electric vehicles - Jaafar, Abdul Hassan; Rahman, Mohammed Ataur; Mohiuddin, A K M; Rashid, Muhammad Mahbubur (IOP Publishing, 2017)
Climate Change is recognized as one of the greatest environmental problem facing the World today and it has long been appreciated by governments that reducing the impact of the internal combustion (IC) engine powered motor vehicle has an important part to play in addressing this threat. In Malaysia, IC engine powered motor vehicle accounts almost 90% of the national greenhouse gas (GHG) emissions. The need to reduce the emission is paramount, as Malaysia has pledged to reduce 40% of CO2 intensity by 2020 from 2005 level by 25% of improvement in average fuel consumption. . The introduction of electric vehicles (EVs) is one of the initiatives. However in terms of percentage, the electric vehicles have not been commonly used by people nowadays and one of the reasons is lack in charging infrastructure especially when cars are on the road. The aim of this study is to simulate and model an advanced charging system for the charging infrastructure of EVs /HEVs all over the nation with slow charging mode with charging current 25 A, medium charging mode with charging current 50 A and fast charging mode with charging current 100 A. The slow charging mode is proposed for residence, medium charging mode for office parking lots, and fast charging mode is called fast charging track for charging station on road. With three modes charger topology, consumers could choose a suitable mode for their car based on their need. The simulation and experiment of advanced charging system has been conducted on a scale down battery pack of nominal voltage of 3.75 V and capacity of 1020 mAh. Result shows that the battery could be charging less than 1 hour with fast charging mode. However, due to limitation of Tenaga Nasional Berhad (TNB) power grid, the maximum 50 A current is considered to be the optimized passive mode for the EV’s battery charging system. The developed advanced charger prototype performance has been compared with the simulation result and conventional charger performance, the maximum variation has been found 15%, this closed agreement between the advanced charger prototype, simulation model and conventional charger validate the prototype model. Furthermore, based on the result presented in this report, the battery to be charged up to 85% of its rated capacity by constant current mode only rather than continue with constant voltage, which could shorten the battery charging time by 16% and prolong the battery life by 10%.